In Reference to Effects of Preoperative Anxiety on Postoperative Delirium in Elderly Patients [Response to Letter] - Ren A (Dove Medical Press, 2021)
Aolin Ren,1,* Na Zhang,1,* He Zhu,1 Kang Zhou,1 Yuan Cao,1 Jindong Liu1,2 1Department of Anesthesiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jindong LiuDepartment of Anesthesiology, Affiliated Hospital of Xuzhou Medical University, Huaihai West Road #99, Xuzhou, Jiangsu, 221000, People’s Republic of ChinaEmail liujindong1818@163.com View the original paper by Dr Ren and colleagues This is in response to the Letter to the Editor